How May Placebo Mechanisms Influence Orofacial Neuropathic Pain?. (July 2019) - Vase, L.; Baad-Hansen, L.; Pigg, M.
The conceptualization of placebo has changed from inactive pills to a detailed understanding of how patients' perception of receiving a treatment influences pain processing and overall treatment outcome. Large placebo effects were recently demonstrated in chronic neuropathic pain, thereby opening the question of whether placebo effects also apply to orofacial neuropathic pain. In this article, we review the new definitions, magnitude, and social, psychological, neurobiologic, and genetic mechanisms of placebo effects in pain, especially neuropathic pain, to illustrate that placebo effects are not simply response bias but psychoneurobiological phenomena that can be measured at many levels of the neuroaxis. We use this knowledge to carefully illustrate how patients' perceptions of the treatment, the relationship with the health care provider, and the expectations and emotions toward a treatment can influence test and treatment outcome and potentially skew the results if they are not taken into consideration. Orofacial neuropathic pain is a new research area, and we review the status on definition, diagnosis, mechanisms, and pharmacologic treatment of neuropathic pain after trigeminal nerve injury, as this condition may be especially influenced by placebo factors. Finally, we have a detailed discussion of how knowledge of placebo mechanisms may help improve the understanding, diagnosis, and treatment of orofacial neuropathic pain, and we illustrate pitfalls and opportunities of applying this knowledge to the test of dental treatments.